Postharvest technology of citrus fruits - Zacarias, Lorenzo; Cronje, Paul J. R.; Palou, Lluís (Elsevier, 2021)
About half of the citrus fruit production in the world is destined to the fresh market. Adequate procedures (time and kind of harvest, handling, processing, storage, and transport) during the whole postharvest chain are absolutely essential to provide good-quality fruit to local and distant markets, extending their commercial period and reducing the postharvest losses. Fruits of the different citrus species and cultivars have a relatively long postharvest life (weeks and even months), but they are very susceptible to develop a large number of postharvest disorders on the peel that depreciate their quality. Moreover, citrus fruits are also prone to decay during the postharvest life due to fungal infections, resulting in large economic losses, but their control is difficult and the cause of public concerns. This chapter also discusses main treatments and operations during the whole postharvest chain, from picking and handling to degreening, packinghouse procedures, transport, and storage temperature and quarantine management.